New perspective on sustained antidepressant effect: focus on neurexins regulating synaptic plasticity - Yuan Ruan; Ruolan Yuan; Jiaqi He; Yutong Jiang; Shifeng Chu; Naihong Chen (Cell Death Discovery, 2024)
Abstract Depression is highly prevalent globally, however, currently available medications face challenges such as low response rates and short duration of efficacy. Additionally, depression mostly accompany other psychiatric disorders, further progressing to major depressive disorder without long-term effective management. Thus, sustained antidepressant strategies are urgently needed. Recently, ketamine and psilocybin gained attention as potential sustained antidepressants. Review of recent studies highlights that synaptic plasticity changes as key events of downstream long-lasting changes in sustained antidepressant effect. This underscores the significance of synaptic plasticity in sustained antidepressant effect. Moreover, neurexins, key molecules involved in the regulation of synaptic plasticity, act as critical links between synaptic plasticity and sustained antidepressant effects, involving mechanisms including protein level, selective splicing, epigenetics, astrocytes, positional redistribution and protein structure. Based on the regulation of synaptic plasticity by neurexins, several drugs with potential for sustained antidepressant effect are also discussed. Focusing on neurexins in regulating synaptic plasticity promises much for further understanding underlying mechanisms of sustained antidepressant and the next step in new drug development. This research represents a highly promising future research direction.